An evaluation of monitoring methods for the endangered giant kangaroo rat - William T. Bean; Robert Stafford; Laura R. Prugh; H. Scott Butterfield; Justin S. Brashares (Wildlife Society Bulletin)
Abstract Accurate, reliable, and efficient monitoring methods for detecting changes in the distribution and abundance of wildlife populations are the cornerstone of effective management. Aerial surveys of active burrow sites and ground counts of open burrows have been used to estimate distribution and abundance, respectively, of a number of rodent species. We compared the efficacy of these and other methods for estimating distribution, abundance, and population growth of the endangered giant kangaroo rat (Dipodomys ingens) to determine the best practices for monitoring. Specifically, we compared aerial surveys, rapid expert assessments, and live‐trapping for estimating giant kangaroo rat range, and burrow counts and live‐trapping for estimating abundance and growth. We carried out the study in the Carrizo Plain National Monument, California, USA, from 2007 to 2011. Expert rapid assessment of sites performed nearly as well as trapping in determining range extent, while aerial surveys provided estimates of total range extent but with less precision. Active burrow counts were adequate to determine relative abundance averaged over multiple years, but were not reliable as an estimate of annual population size or growth. © 2012 The Wildlife Society.